Long-term conditions, multimorbidity, lifestyle factors and change in grip strength over 9 years of follow-up: Findings from 44, 315 UK biobank participants. (15th October 2021) - Hurst, Christopher; Murray, James C; Granic, Antoneta; Hillman, Susan J; Cooper, Rachel; Sayer, Avan Aihie; Robinson, Sian M; Dodds, Richard M
Abstract: Background: Weak grip strength is associated with a range of adverse health outcomes and an accelerated decline in grip strength confers an even greater risk. The factors associated with change in grip strength in mid-life remain to be fully determined. Methods: We used data from 44, 315 UK Biobank participants who had grip strength measured at baseline (2006-10) and a subsequent visit approximately nine years later. At baseline, participants' long-term conditions (LTCs) were categorised against a hierarchy, with multimorbidity characterised by the number of LTC categories. Lifestyle factors were assessed. Change in grip strength was grouped into four patterns: decline, stable low, stable high or reference (no change or increase) and used as the outcome in multinomial logistic regression. Results: Most LTC categories were associated with adverse patterns of change in grip strength (stable low and/or decline): for example, musculoskeletal/trauma conditions were associated with an increased risk of the stable low pattern (Relative Risk Ratio [RRR] = 1.63; 95% confidence interval [CI]: 1.49-1.79). Multimorbidity and lifestyle factors had independent associations with grip strength change. Those with 3+ categories of LTCs were more likely to experience decline in grip strength (RRR = 1.18; 95% CI: 1.08-1.28) compared to those with none. Low physical activity was associated with adverse patterns of grip strength, while raised body mass index (BMI) had divergent associations. Conclusions: Individuals living with multimorbidity and those with lifestyle risk factors such as low physical activity are at increased risk of low muscle strength and the loss of strength over time.